2014
DOI: 10.1186/1472-6920-14-s1-s9
|View full text |Cite
|
Sign up to set email alerts
|

Resident duty hours in Canada: a survey and national statement

Abstract: Physicians in general, and residents in particular, are adapting to duty schedules in which they have fewer continuous work hours; however, there are no Canadian guidelines on duty hours restrictions. To better inform resident duty hour policy in Canada, we set out to prepare a set of recommendations that would draw upon evidence reported in the literature and reflect the experiences of resident members of the Canadian Association of Internes and Residents (CAIR). A survey was prepared and distributed electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…In contrast, Basel residents are subject to a much stricter RDHR with less formal training time. This fact may be seen as a less favorable environment for optimal surgical training quality, confirming articulated concerns and findings of other studies [9][10][11]14,21,40 . However, deployment of alternative working patterns can help to overcome this shortcoming 13 , without decline in surgical competence 15 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, Basel residents are subject to a much stricter RDHR with less formal training time. This fact may be seen as a less favorable environment for optimal surgical training quality, confirming articulated concerns and findings of other studies [9][10][11]14,21,40 . However, deployment of alternative working patterns can help to overcome this shortcoming 13 , without decline in surgical competence 15 .…”
Section: Resultssupporting
confidence: 82%
“…Queen's residents work significantly longer compared to their Basel colleagues, reflecting the findings of other studies 17,21 . However, especially consultants at both Queen's and Basel expressed concern about the impact of RDHR on the number of performed surgical procedures, a finding reported in other studies [9][10][11]14,21,40 . As a consequence, the majority of Swiss' and Queen's surgical residents self-reported that they circumnavigated the imposed RDHR by "volunteering" for additional work hours.…”
Section: Resultsmentioning
confidence: 94%
“…There have been no Canadian guidelines on duty hour restrictions [11]. However, each province has its own regulations.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Argument, że lekarze nie chcą pracować ponad swoje możliwości, jest zrozumiały, ale musi zostać skonfrontowany z wymaganiami systemowymi, albowiem zbyt mała liczba lekarzy wiąże się z ryzykiem dla pacjentów. Z powodu braku rozwiązań legislacyjnych problem pozostaje nierozwiązany [23][24][25].…”
Section: Wnioskiunclassified